Perspektif Komunikaksi Islam Terhadap Perilaku Kekerasan Verbal Dalam Permainan Daring (Studi Kasus Game Mobile Legends: Bang Bang) - Abdu Zikrillah; Aditia Muara Padiatra; Indra Gunawan; Bambang Setiawan; Muhamad Zaenal Muttaqin (Jurnal Dakwah dan Komunikasi, 2021)
In everyday life in the present, it is common for young people or teenagers to play online games. In playing online games there is communication in it which is not uncommon verbal violence. This study examines the Islamic perspective in seeing verbal violence that often occurs in online game play, which in this case is represented by the MOBA Mobile Legends Bang-Bang game. The research method uses content analysis techniques with a descriptive discussion. The communication process is seen based on the recordings of game players uploaded via YouTube and other social media. There are several factors that cause verbal violence in playing online games from several points of view, namely moral knowledge, the need to be recognized, the character of cyberspace environments, equality and a sense of belonging, and parenting. Verbal violence that often occurs in online gaming is accusing and blaming, undermining, discounting, and name calling. In Islamic teachings there are six directives as principles for communicating well, namely Qawlan Sadîdan (words that are polite and kind), Qawlan Balîghan (words that make an impression on the soul, and are right on target), Qawlan Maisûrâ (light words), Qawlan Layyina (gentle words), Qawlan Karîma (noble words), Qawlan Ma'rûf (good word or appropriate expression).